Oath of loyalty - Mills, Kyle, 1966-; Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel, 2022)
"With President Anthony Cook convinced that Mitch Rapp poses a mortal threat to him, CIA Director Irene Kennedy is forced to construct a truce between the two men. The terms are simple: Rapp agrees to leave the country and stay in plain sight for as long as Cook controls the White House. In exchange, the administration agrees not to make any moves against him. This fragile détente holds until Cook's power-hungry security adviser convinces him that Rapp has no intention of honoring their agreement. In an effort to put him on the defensive, they leak the true identity of his partner, Claudia Gould. As Rapp races to neutralize the enemies organizing against her, he discovers that a new generation of assassins is on her trail. A killer known to intelligence agencies only as Legion. The shadowy group has created a business model based on double-blind secrecy. Neither the killer nor the client knows the other's identity. Because of this, Legion can't be called off nor can they afford to fail. No matter how long it takes--weeks, months, years--they won't stand down until their target is dead. Faced with the seemingly impossible task of finding and stopping Legion, Rapp and his people must close ranks against a world that has turned on them"--Dust jacket flap.